Policing Gender, Class And Family In Britain, 1800-1945 - Mahood, Linda (Women's and Gender History, 1995)
This book is intended for undergraduate courses on modern British history, women's history, courses on family, sexuality and childhood. Women's studies, history of education, sociology.